Evaluation of the effects of manuka honey on salivary levels of mutans streptococci in children: A pilot study - S Rupesh; J J Winnier; U A Nayak; A P Rao; N V Reddy; J Peter (Wolters Kluwer Medknow Publications, 2014)
Background: There has been much debate in the past about whether honey is harmful to the teeth, mostly as part of the debate about raw sugar versus refined sugar and the results have been equivocal. However, what has not been taken into account is that honey varies markedly in the potency of its antibacterial activity. Manuka (Leptospermum scoparium) honey from New Zealand has been found to have substantial levels of non-peroxide antibacterial activity associated with an unidentified phytochemical component, denoted as Unique Manuka Factor (UMF). Aims: Considering the potential antimicrobial effects of manuka honey, the present study attempted to investigate effects of twice daily use of manuka honey with UMF 19.5 on salivary levels of Mutans streptococci in children. Study Design: The investigation was a stratified comparison of two parallel groups of children who either used manuka honey with regular tooth brushing regimen or continued only with regular tooth brushing regimen twice daily under professional supervision for a 21-day period. A total of three salivary samples were taken from each individual at baseline, day 10, and day 21; colony counts of Streptococcus mutans (S. mutans) were determined. All data was subjected to paired T-test and Wilcoxon's signed ranks sum for intra- and intergroup comparisons respectively. Results: Children using manuka honey showed statistically significant reductions in salivary S. mutans after 10 and 21 days. Conclusion: Manuka honey with UMF 19.5 may be considered as an effective adjunctive oral hygiene measure for reducing colony counts in children.